Reward activates stimulus-specific and task-dependent representations in visual association cortices. - Schiffer, A; Muller, T; Yeung, N; Waszak, F (2014)
Humans reliably learn which actions lead to rewards. One prominent question is how credit is assigned to environmental stimuli that are acted upon. Recent functional magnetic resonance imaging (fMRI) studies have provided evidence that representations of rewarded stimuli are activated upon reward delivery, providing possible eligibility traces for credit assignment. Our study sought evidence of postreward activation in sensory cortices satisfying two conditions of instrumental learning: postreward activity should reflect the stimulus category that preceded reward (stimulus specificity), and should occur only if the stimulus was acted on to obtain reward (task dependency). Our experiment implemented two tasks in the fMRI scanner. The first was a perceptual decision-making task on degraded face and house stimuli. Stimulus specificity was evident as rewards activated the sensory cortices associated with face versus house perception more strongly after face versus house decisions, respectively, particularly in the fusiform face area. Stimulus specificity was further evident in a psychophysiological interaction analysis wherein face-sensitive areas correlated with nucleus accumbens activity after face-decision rewards, whereas house-sensitive areas correlated with nucleus accumbens activity after house-decision rewards. The second task required participants to make an instructed response. The criterion of task dependency was fulfilled as rewards after face versus house responses activated the respective association cortices to a larger degree when faces and houses were relevant to the performed task. Our study is the first to show that postreward sensory cortex activity meets these two key criteria of credit assignment, and does so independently from bottom-up perceptual processing.